Sosialisasi Pasar Modal “Investasi Cerdas di Era Digital” bagi Siswa/i SMK N 8 Kota Padang - Anggraini, Dina; Sartika, Dewi; Mulyani, Fitrah; Dahar, Reni; Yanti, Nino Sri Purnama; Valentina K, Yunita (Jurnal Pengabdian Masyarakat Dharma Andalas, 2024)
Understanding the investment society is needed by means of continuous socialization involving various parties so that understanding of capital market literacy to the community can continue to grow, namely by socializing to the public, especially the millennial generation that investing in the capital market is easy, planned, and cheap. The introduction of capital market literacy as a means of saving shares for vocational students aims to educate students as a millennial generation to be interested in capital market investment so that it is hoped that students can be interested in participating in capital market investment education and then be interested and interested in saving shares by opening a capital market account. The method of implementing community service activities in the form of providing learning to partners in the form of capital market socialization "Smart Investment in the Digital Age" material to students of SMK N 8 Padang City